Makna Budaya dalam Dongeng Humor Masyarakat Banten - M A Tihami (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2015)
This article examines humour stories frequently told by the Bantenese. The main problems discussed here are: What kind of humour stories that spread among the Bantenese? What are the functions and meanings of the stories for the people? How do people understand and make use the stories? This article is the result of a set of fieldwork using ethnographic method with anthropological approach. In analyzing data, I use functional–structural approach. The methods used in collecting data are library research, participant observations, and in–depth interviews. Based on research findings, I conclude that there are at least 41 humour stories and 15 most popular themes. Meanwhile, based on its functions, there are at least 8 functions in the stories, namely as a set of advice pertaining moral values, as social critiques, to control attitude and behavior, to influnce people, to entertain, as tools to deal with boredom and stress, as tools to evaluate one’s mistakes, and as tools to select what is appropriate for the local society. Keywords: Banten, Folklore, Humour Stories, Local Culture, Popular, Culture.